The apple pie that Papa baked - Thompson, Lauren, 1962-; Bean, Jonathan (New York : Simon & Schuster Books for Young Readers, 2007)
Papa grows his own apples and bakes them into a delicious pie.
Keywords: Food -- Juvenile fiction; Trees -- Juvenile fiction; Apples -- Juvenile fiction